Association between knee-to-hip flexion ratio during single-leg vertical landings, and strength and range of motion in professional soccer players. Issue 3 (3rd May 2020) - Leporace, Gustavo; Tannure, Marcio; Zeitoune, Gabriel; Metsavaht, Leonardo; Marocolo, Moacir; Souto Maior, Alex
Abstract: The aim of this study was to test the correlation between knee-to-hip flexion ratio during a single leg landing task and hip and knee strength, and ankle range of motion. Twenty-four male participants from a professional soccer team performed a continuous single leg jump-landing test during 10s, while lower limb kinematics data were collected using a motion analysis system. After biomechanical testing, maximal isometric hip (abduction, extension, external rotation), knee extension and flexion strength were measured. Maximum ankle dorsiflexion range of motion was assessed statically using the weight bearing lunge test. Pearson correlation coefficients were calculated to determine the associations between the predictor variables (knee and hip strength, and ankle ROM) and the main outcome measure (knee-to-hip flexion ratio). Correlation between knee-to-hip flexion ratio and hip abductors strength was significant ( r  = −0.47; p  = 0.019). No other significant correlations were observed among the variables ( p  > 0.05). These results demonstrated that a lower hip abductors strength in male soccer players was correlated with a high knee-to-hip flexion ratio during landing from a single leg jump, potentially increasing knee overload by decreasing energy absorption at the hip. The results provide a novel proposal for the functioning of hip muscles to control knee overload.